Historical commentary for the bilingual edition of the chronicle (Historia Salonitana) of Thomas the Archdeacon of Split - Matijević Sokol, Mirjana (2006)
Historical commentary for the bilingual edition of the chronicle of Thomas the Archdeacon of Split
Projekt MZOS
Projekt MZOS
Projekt MZOS
ENG